Stressors among Students of a School of Rupandehi, Nepal - Anuja Kachapati; Laxmi Pathak; Kavita Lamichhane; Sharmila Bhandari; Shristee Rawal; Bhagwati Thapa; Sigma Bhattarai (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION The American Institute of Stress (2018) defines stress as an emotional disturbance or change caused by stressors. According to the World Health Organization (WHO), approximately 4% of the global population experiences anxiety and stress disorders. Students often face incompatibility between their mental, physical, and social development, as well as difficulties adapting to their environment. Such challenges may lead to psychological problems and deviant behaviors. MATERIAL AND METHODS A cross-sectional study was conducted to determine the level of stress and its stressors among 175 students at Namuna Secondary School, Bhairahawa, Nepal. A random sampling technique was used. Data were collected using the Perceived Stress Scale-14 and pre-tested semi-structured questionnaire. Analysis was performed using descriptive and inferential statistics with SPSS version 16. RESULTS The study findings revealed that, 44% of students experienced mild stress, while 56% students experienced moderate stress. Bivariate logistic regressions analysis indicated associations between the level of stress and frequency of examination (AOR=2.36, 95% CI:1.102-5.061, p=0.027), poor parental relation (AOR=2.13, 95% CI: 1.014-4.509, p=0.046) and inability to fulfill basic needs (AOR= 2.11, 95% CI: 1.049-4.258, p=0.036). CONCLUSION Stress among school children is a growing concern in today’s fast-paced and competitive world. Addressing stress among school children is essential for their overall development. Parents, teachers, and society must work together to create a nurturing environment that fosters both academic success and emotional well-being.